Excellence In E-Governance: Replicable Innovations from Quezon City - . Pacaño, Jr., Edgar A; Tayaoan, Harold May B.; Molina, Kenneth Anthony; da Costa, Estefânia L. S.; Neverio, Norman A.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study explores how Quezon City’s e-governance programs—QC e-services, QCitizen ID, and QC Biz Easy—have improved public ser-vice delivery by making services more efficient, transparent, and accessible. These initiatives offer practical benefits, including easy-to-use interfaces and broad device accessibility, making them adaptable for other Local Government Units (LGUs) interested in digital transformation. The research also addresses challenges, such as limited technology access, funding constraints, and the need for strategies to manage resistance to change. Findings show that Que-zon City’s approach not only enhances local services but also sets a benchmark for other municipalities seeking to innovate and im-prove public service delivery through e-governance.